Editorial - Office, Editorial (Medicina Historica, 2019)
The 52nd National Congress of our Society, successfully organized to perfection by Professor Michele Riva of the Bicocca University, in Monza from the 12th to 14th June, is the ultimate proof of our vitality and our scientific industriousness. During the three days many Italian medicine historians were involved.[....]